A neurocutaneous island flap model: An experimental study in rats - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
Neurocutaneous flaps have been popularized recently in clinical reconstructive surgery. However, controversies exist concerning their anatomy and physiology. The particular role of neural vasculature in the survival of these skin flaps is also quite undefined in the experimental setting, and additional studies on this subject are necessary. The goal of this study was to describe a neurocutaneous flap in a rat model and to investigate its blood supply. Thirty male Sprague-Dawley rats weighing 300 to 350 g were used in this study, which was conducted in two stages. During the first stage, the lower extremities of 10 rats were dissected for the anatomic study of the neurocutaneous flap. A constant cutaneous nerve innervating the anterolateral thigh skin was exposed. It arose either from the saphenous nerve or the superficial epigastric nerve and was accompanied by a constant longitudinal arterial plexus. The tiny neural vessels were conveyed by the superficial fascia along their course. A 30 x 30-mm cutaneous island flap, which was based only on the cutaneous nerve with its accompanying vessels and a strip of superficial fascia, was raised on the anterolateral thigh skin using an operating microscope. The well-perfused skin territory was marked after sodium fluorescein injection. The stained skin territory was located centrally and medially on the whole island flap, and it was approximately 10 x 20 mm, This finding was confirmed by the qualitative assessment of the vascularity for this skin territory in microangiography. After studying the pedicle anatomy and determining the optimal viable skin island, the second stage of the study was performed. The remaining 20 rats were divided into two groups. In the experimental group (N = 10), a neurocutaneous island flap (10 x 20 mm) was outlined on the anterolateral aspect of the thigh at its middle third, It was designed in such a way that its short and long axes ray in the center of the distance between the anterior superior iliac spine and the anterior aspect of the knee joint. After identification and dissection of the neurovascular pedicle, the flap was raised in a lateral-to-medial direction without including the deep fascia. At this point the flap remained connected only by the pedicle and a strip of superficial fascia surrounding it. It was sutured in the same place. In the control group (N = 10), the pedicle of the flap was severed and the skin island was sutured back as a composite graft. All the experimental flaps survived well. In the control group, none of the flaps survived except one that was partially viable. The flaps in the experimental group were reelevated as neurocutaneous island flaps on day 7 for microangiographic study, and specimens were processed for histologic staining. Microangiography revealed the extent of neural vasculature and vascularization of the skin through cutaneous perforators. Histologic investigation demonstrated the neural vessels that were related closely to the superficial fascia. The authors propose a neurocutaneous island flap model in the lower extremity of the rat in which the survival of the flap depended mainly on the neural arterial supply, It was also demonstrated that the superficial fascia played a role as a connective tissue framework for conveying tiny neural blood vessels to reach the skin. This model may serve as a reproducible and reliable neurocutaneous island flap model for additional studies in this field.
Keywords: FASCIOCUTANEOUS FLAP; FOREARM; NERVES; LEG